A Translation Analysis Of Interrogative Sentences In Born Under A Million Shadows Novel And Its Translation - Prasmawati, Maratina Indah, Dr. Anam Sutopo, M.Hum, Mauly Halwat Hikmat, Ph. D (2014)
This research focuses on analyzing the interrogative sentences found in Born Under A Million Shadows novel and its translation. The objectives are to describe the types of interrogative sentences found in Born Under A Million Shadows novel and its translation, and to describe the equivalence of interrogative sentences found in Born Under A Million Shadows novel with its translation. This research applies descriptive qualitative method. The data are the interrogative sentences found in Born Under a Million Shadows novel and its translation. The data sources are the novel entitled Born Under a Million Shadows and its translation "Dalam Sejuta Bayangan". The way to collect data is using docummentation method. The results of the research show that, firstly, there are three types of interrogative sentences found in Born Under a Million Shadows novel namely, yes-no questions, questions tag or attached questions, and interrogative-word questions. From 226 data, there are 69 or 30,5% data belong to yes no questions (36 data or 15,9% data belong to yes-no questions with tense auxiliary, 26 data or 11,5% data belong to yes-no questions with do auxiliary, and 7 data or 3,1% data belong to yes-no questions with modal auxiliary ), 22 data or 9,7% data belong to question tag or attached questions. 135 data or 59,7% data belong to interrogative-word questions (11 data or 4,8% data of Who, 55 data or 24,3% data of What, 10 data or 4,4% data of Where, 23 data or 10,1% data of Why, 36 data or 15,9% data of How).). It means that the most dominant of the occurance is the interrogative-word question. It also shows the characters in the novel want to get a lot of information. Secondly, the equivalence of the data is categorized into equivalent translation and non-equivalent translation. From 226 analyzed data, 219 data or 96,9% data include equivalent translation. There are 67 data or 29,6% data of yes-no questions (34 data or 15,04% data of yes-no questions with tense auxiliary, 26 data or 11,5% data of yes-no questions with do auxiliary, and 7 data or 3,1% data in yes-no questions with modal auxiliary),22 data or 9,7% data of question tag or attached questions, 130 data or 57,5% dataof interrogative-word questions (10 data or 4,4 % data of Who, 52 data or 23% data of What, 10 data or 4,4% data of Where, 22 data or 9,7% data of Why, 36 data or 15,9 % data of How). The data include non-equivalent translation are 7 data or 3,1% data. So, the translation of interrogative sentences found in Born Under a Million Shadows novel is excellent.